2014
DOI: 10.1097/bot.0000000000000032
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Bony Pelvic Exposure Through the Modified Stoppa Approach

Abstract: The modified Stoppa approach allows for exposure of most (79%) of the inner true bony pelvis including the entire pelvic brim and 80% of the quadrilateral surface. On average, visualization is possible 2 cm above the pelvic brim and 5 cm below the pelvic brim along the quadrilateral surface, providing adequate anterior exposure for clamp and implant placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…In light of these 2 limitations, human cadaver dissections are well established as a reliable method for defining anatomic relationships and comparisons. 7,[26][27][28] Although this study used advanced digital imaging software, it relied on 2-dimensional images to approximate the surface area of 3-dimensional structures. Additionally, all photographs were taken from the best view of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these 2 limitations, human cadaver dissections are well established as a reliable method for defining anatomic relationships and comparisons. 7,[26][27][28] Although this study used advanced digital imaging software, it relied on 2-dimensional images to approximate the surface area of 3-dimensional structures. Additionally, all photographs were taken from the best view of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…1C). Contrary to the initial description of the screw insertion technique by Culemann et al [7], with more surgical experience and optimized retractors, the area for the screw entry point can be visualized [2] and the infraacetabular screw placed through the anterior intrapelvic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional, modified Stoppa, ilioinguinal and iliofemoral approaches are often used to treat acetabular and pelvic ring fractures, with a fairly good success rate (70-95 %) and low rates of complications (Karunakar et al, 2004;Balbachevsky et al, 2006;Kacra et al, 2011;Bible et al;Court-Brown et al, 2014;Jensen et al, 2015). Despite that, some studies showed vascular injury rates of 6.2 % of patients with CM (Jensen et al).…”
Section: Discussionmentioning
confidence: 99%
“…Among other structures that should be identified are the external iliac artery and the superior gluteal neurovascular bundle (Bible et al, 2014).…”
Section: Discussionmentioning
confidence: 99%